Intravenous esketamine in pediatric Rett syndrome: An open-label, early phase 1 pilot study - Huiping Li; Shu Liu; Caimei Lin; Yuchao Wu; Xiuping Wu; Yukun Huang; Yajun Wu; Xiubin Tong; Xiu Xu (Molecular Therapy: Methods & Clinical Development)
Rett syndrome (RTT) is a severe neurodevelopmental disorder. N-Methyl-d-aspartate receptor (NMDAR) antagonism has shown therapeutic potential in preclinical RTT models. We performed a pilot study to explore whether intravenous esketamine, an NMDAR antagonist, alleviates the symptoms of pediatric RTT. This was a prospective, single-arm, single-site, open-label, early phase 1 pilot study. Three girls with classic RTT aged 5–10 years were enrolled. Esketamine was intravenously administrated once per week for 5 weeks. The efficacy assessments included RTT-related questionnaires and video electroencephalograms (VEEGs). Prespecified adverse events (AEs) were monitored using clinical observations and standard laboratory tests. The treatment with intravenous esketamine was generally well tolerated and safe, with some patients experiencing mild AEs, including self-alleviating nausea, vomiting, and irritability. Three participants showed minimal improvements in their Clinical Global Impression Scale-Improvement, Rett Syndrome Behavior Questionnaire, and Revised Motor Behaviors Assessment Scale scores. However, individual differences were observed in the efficacy measures. VEEGs indicated gradual increases in posterior dominant rhythm peak frequency throughout the intervention. This pilot study highlights the potential of esketamine treatment for improving behavioral dysfunction in patients with RTT. Investigating the appropriate dosage form of esketamine may enhance its beneficial effects in RTT with fewer undesirable features.